Peningkatan Pengetahuan Petani melalui Transfer Teknologi Budidaya Padi di Desa Bagok, Kabupaten Barito Timur, Kalimantan Tengah - Daniel March Stephen Nainggolan; Tri Budiarto; Edi Wiraguna (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Indonesia is known as an agrarian country with abundant natural resources; however, challenges remain in achieving food security, particularly in rice production. Bagok Village, East Barito Regency, Central Kalimantan, has considerable potential for rice cultivation, yet farmers face constraints such as limited knowledge of cultivation practices, restricted access to technology, and insufficient training or extension support. This study aims to analyze the improvement of farmers’ knowledge after participating in technology transfer activities. A qualitative approach supported by quantitative data was employed, with data collected through observation, interviews, focus group discussions, questionnaires, and documentation. Data were analyzed using a process of reduction, presentation, and conclusion drawing. The results show significant improvements in farmers’ knowledge across three key aspects: rice cultivation based on Good Agricultural Practices (GAP) increased by 57.6%, water management by 54.98%, and pest and disease control by 35%. These findings highlight the importance of continuous and participatory training to encourage the adoption of agricultural innovations. Overall, technology transfer activities have proven effective in strengthening farmers’ capacity to manage rice fields more efficiently, thereby supporting national food security efforts.